Possession of Smartphones while Studying: Effects on the Recall of Information in a Sample of Psychology Students - Zarevičiūtė, Lela; Jarašiūnaitė - Fedosejeva, Gabija (Psichologija, 2024)
The impact of smartphones on people’s daily lives is increasing. However, despite the benefits of smartphones, the adverse effects of these devices are becoming more prominent in the academic environment; therefore, it is important to analyse them. The aim of the research is to evaluate the effects that possessing of a smartphone while studying has on the recall of information in a sample of psychology students. The research analysed data collected from a sample of 80 second and third-year students from the bachelor’s program in psychology (69 females, 10 males, and 1 “other”). The age of the participants varied from 19 to 54 years (average age – 24 years, std. deviation – 7.93 years). Research method: experiment. The participants were divided into groups, according to the effects: 1) those who could not have their smartphones during the lecture; 2) those who could have their smartphones during the lecture but were asked not to use them; 3) those who could have their smartphones during the lecture and were not given any instruction on their usage. During each experiment session, 8–13 students from each group watched a 20-minute lecture recording. After the lecture, the participants completed a short test on the lecture’s content. After finishing the test, the participants filled in a nomophobia questionnaire (Yildirim & Correia, 2015). One week after participating in the experiment, students sent in a screenshot with the information on their average smartphone screen time. Students who had their smartphones during the lecture recalled the information worse than those who did not. However, no significant differences were found between the group of students who were given instructions on the usage of smartphones and those who were not. The results also revealed that a higher average time spent using a smartphone was associated with poorer recall of lecture information.